Early Detection of Biliary Atresia through Quantitative Ultrasound Imaging: A Retrospective Analysis of Key Diagnostic Features - Violetta, Lenny; Nurhayati, Dian; Elmanar, Ryan (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2025)
Biliary atresia (BA) is a progressive fibroinflammatory obstruction of the intra- and extrahepatic bile ducts, accounting for approximately 25–30% of neonatal cholestasis cases worldwide. Delayed diagnosis significantly increases the risk of liver failure and the need for transplantation. This study aimed to evaluate the diagnostic value of specific ultrasonographic parameters triangular cord sign, hepatic artery to portal vein (HAD/PV) ratio, and hepatic subcapsular flow (HSF) in the early detection of BA. A retrospective observational analytic study was conducted at Dr. Soetomo General Academic Hospital, involving 82 neonates with cholestasis between January 2019 and December 2023. Ultrasound images acquired using the GE LOGIQ Series E9 XDClear 2.0 were reviewed by blinded pediatric radiology consultants via the HOROS DICOM viewer. Statistical analysis revealed that both the triangular cord sign (p = 0.024; OR = 3.158) and hepatic subcapsular flow (p = 0.003; OR = 5.635) showed significant association with BA, while the HAD/PV ratio did not reach statistical significance (p = 0.087). Triangular cord sign and hepatic subcapsular flow are reliable sonographic markers that support early diagnosis of biliary atresia, whereas the HAD/PV ratio showed limited diagnostic relevance in this cohort. These findings reinforce the utility of non-invasive ultrasound imaging in differentiating BA from other causes of neonatal cholestasis. Incorporating these parameters into routine neonatal screening protocols may facilitate earlier surgical intervention and improve long-term outcomes